An Interaction between Tourism enabling environment, Investment in tourism and poverty reduction in communities around protected areas The case study of Bushenyi district, south-western Uganda - Tukamushaba, Eddy K.; Katongole, Celestine (My University, 2007)
The study was carried to examine the relationship between tourism enabling environment, investment in tourism and tourism related sectors, and poverty reduction in communities around protected areas. It was guided by four objectives of examining the relationship between tourism education and training and growth of indigenous capabilities, the relationship between community participation and involvement in tourism planning and development and community empowerment, the relationship between government political will and commitment and growth of tourism support infrastructure and the relationship between community empowerment and poverty reduction. The study took a cross section study design and the questionnaires were filled by the respondents with the help of trained research assistants. A sample of 310 was used. The findings revealed that there was a significant relationship between tourism enabling environment, investment in tourism and tourism related sectors, and poverty reduction. The key recommendation was to always involve local communities in planning and development of new tourism activities through organisation of community workshops, and seminars where people should be able to share their views on activities that will eventually affect them.
Keywords: Poverty reduction; community involvement; conflict management; tourism